Determinants that empower the public understanding on Waqf concept: case study in Kajang, Selangor / Muhamad Afifuddin Azham - Azham, Muhamad Afifuddin (2017)
Muslim around the worlds are exposed to the Waqf practice, but what is actually the Waqf It is basically an Islamic voluntary action and financing instrument which is significantly the development of economic and social order of Muslim community in the past. In general, the awareness in practicing the Waqf concept among Muslim society are important since it is valuable to Muslim and very useful in helping those needy people. In Malaysia there are increasing on the number who participate on the waqf but it still to have merely mild contribution particularly to the improvement of Muslim community in Malaysia. Based on Scholar reviews, several explanations and suggestions for improvement were discussed and offer to solve this problems. One of the issues highlighted was because of low level of understanding among the local Muslim on the concept of Waqf. Due to such scenario many parties must take action to monitor the development of Waqf Education in Malaysia in order to show good level of understanding on Waqf concept. Therefore, the implication of this study is to identify the components that can impact the level of understanding on Waqf idea among a group of certain people in Malaysia. Through this research, a basic Theoretical Framework from the past research will be used as a main source to get the results and hopefully this research can be used to improve the Islamic economy of Malaysia in future. Based on this research its came out to have positive variable on perceived behavior control, religiosity and awareness regarding to factor that influence public understanding on Waqf concept. Meanwhile amount of information came out to give no significant relationship toward determinant that empower public understanding on waqf concept.